195 Functional Defects Identified in Outgrowth Endothelial Cells from Diabetic Patients Compared to Healthy Controls. (3rd June 2016) - Hasan, Ahmad; Weston, Ria; Wilkinson, Fiona L; Boulton, Andrew; Rashid, Tawqeer; Bowling, Frank; Alexander, MY vonne
Abstract : Background: Circulating endothelial progenitor cells (EPCs) are thought to play a pivotal role in endothelial repair. Clinical trials utilising EPCs to promote therapeutic angiogenesis are already underway Previous reports suggest a reduced EPC number and impaired functional activity in patients with type 2 diabetes mellitus. However, the actual identity of the cell type involved and the functional role played in the repair process needs to be further defined before EPCs can be successfully utilised in the clinic. In the present study, we assessed the functional capacity of circulating late out-growth endothelial progenitor cells (OECs) to further assess the contribution of the diabetic environment to diminished OEC function in the context of wound healing. Methods and results: OECs were isolated from 7 diabetic patients, presenting with ulcers ranging in size from 60 mm 3 –2500 mm 3 . OECs were characterised as CD34 +, CD31 +, vWF+, positive for AcLDL and UEA uptake and negative for the hematopoietic marker CD45 by immunohistochemistry. Migration of CD34 + OECs, evaluated by a scratch assay, demonstrated that migration is impaired in diabetic OECs compared to healthy control OECs, with 40–42% closure vs 100% over 24 h respectively. In addition, achemotaxis transwell migration assay showed a decreased response to SDF-1 by diabetic cells vs healthy OECs. An angiogenesis tube formation assay also established a reduced capacity of the diabetic OECs to form an endothelial network as compared to healthy OECs (p < 0.0001), measured using the closed loop perimeter, and the number of branch points (p < 0.05). Nitrite concentrations were measured using a Griess assay, and the results showed that diabetic OECs produced less nitric oxide as compared to healthy OECs (p < 0.0005). Conclusion: OECs from diabetic patients show an impaired migration and response to chemotactic agents in vitro compared to OECs isolated from healthy controls. In addition, the reduced nitric oxide bioavailability found by diabetic cells may contribute to OEC dysfunction in diabetes. Future work will focus on assessing the secretome of healthy vs diabetic OECs.